Structural, electronic structure and magnetic studies of SmFe1-xNixO3 (x <= 0.5) - Bashir, Abida; Ikram, M.; Kumar, Ravi; Lisboa Filho, Paulo Noronha [UNESP]; Thakur, P. (Elsevier B.V., 2010)
We present the structural, electronic structure and magnetic studies of Ni doped SmFeO3. The X-ray diffraction (XRD) studies confirm the single phase nature of the samples having orthorhombic Pbnm structure and the unit-cell volume is decreasing with the increase of Ni concentration. X-ray absorption spectroscopy (XAS) studies on O K. Fe L-3.2, Ni L-3.2 and Sm M-5.4 edges of SmFe1-xNixO3 (x <= 0.5) samples along with the reference compounds revealed the homo-valence state of Fe and Ni in these materials. From magnetization studies it has been observed the materials exhibit ferromagnetic and anti-ferromagnetic sub-lattices, which are strongly dependent on the thermo-magnetic state of the system. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: XRD; X-ray absorption spectroscopy; Magnetization